2008
DOI: 10.4103/0256-4602.42812
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Efficient Resource Allocation Algorithm for Multiuser OFDM Systems

Abstract: The key issues in the design of a multiuser orthogonal frequency division multiplexing (MU-OFDM)-based systems are the subcarrier, power, and the bit allocation. Conventionally, the sum capacity of MU-OFDM is maximized when each subchannel is assigned to the user with the best channel-to-noise ratio for that subchannel, with power subsequently distributed by water-filling algorithm. In this paper, several adaptive resource allocation techniques for multiuser OFDM system under various constraints are analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 8 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Subchannel allocation based on auction algorithm was proposed by [16], in which it was found that throughput was sustained at the cost of user data rates. A novel efficient resource allocation algorithm for multiuser OFDM system using a proportional based algorithm among users and to achieve good performance even with low SNR was proposed by [17].…”
Section: Introductionmentioning
confidence: 99%
“…Subchannel allocation based on auction algorithm was proposed by [16], in which it was found that throughput was sustained at the cost of user data rates. A novel efficient resource allocation algorithm for multiuser OFDM system using a proportional based algorithm among users and to achieve good performance even with low SNR was proposed by [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, auction algorithm use to allocate subchannel to the appropriate most user who require that subchannel. A novel efficient resource allocation algorithm for multiuser OFDM system using a joint allocation method and root finding algorithm to achieve good performance even with low signal to noise ratio (SNR) was proposed by [3]. Another interesting paper with adaptive resource allocation based on modified GA and particle swarm optimization (PSO) for multiuser OFDM system was proposed by [4].…”
Section: Introductionmentioning
confidence: 99%